Planning System Gauge Strength Wind Based on the Internet of Things - Ari Wibowo, Aziz; Hardyanto, R. Hafid; Wahyu Ciptadi, Prahenusa; Harry Pratisto, Eko (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2024)
The wind moves air​ from place One to somewhere else because there exists a different pressure of air. There are many​ benefits of wind for creatures living in the world, especially humans among them use wind by fishermen, generators of electricity power wind, and sports flight like kites.​ Prevention of disaster Because wind only can give warning to minimize casualties and damage in the area that occurs nipple pickaxe namely Anemometer as gauge speed wind. Besides a lot of benefits wind, however own impact bad adverse winds​ man. This tool is designed To measure the speed of the wind as well as minimize disasters caused by wind.​ This tool uses the ESP32 microcontroller as the main connected system through device wifi as Anemometer connections and sensors used as gauge strength wind, connected web server with a microcontroller via wifi as an interface for monitoring. Making tools using the data collection method used that is literature study, observation, and interviews. The system development stage consists of analysis, implementation system design as well as testing. Testing on the system is carried out with a test Anemometer sensor in an open area with monitoring using a connected web server with a microcontroller via wifi site testing with exists tool This measuring system design strength wind based on the Internet of Things.